Authors and their public in ancient times - Putnam, George Haven, 1844-1930 (Salt Lake City, UT : Project Gutenberg, 2024)
"Authors and their public in ancient times: a sketch of literary conditions" by Geo. Haven Putnam is a historical account written in the late 19th century. The work explores the literary landscape of ancient civilizations, analyzing the relationships between authors, their works, and the public up until the fall of the Roman Empire. The book's aim is to outline how authors were compensated for their literary productions and to provide a historical context for what is now understood as literary property. The opening of the text introduces the author's intent to provide a preliminary overview of the literary conditions in ancient times. It emphasizes the evolution of literature from oral traditions to written forms, pointing out that literary property$1 (Bconceptualized as ownership of ideas and remuneration for authors$1 (Bdid not truly emerge until much later in history, particularly after the advent of the printing press. The initial chapters delve into the earliest forms of literature found in cultures such as Chaldea and Egypt, offering insight into how these civilizations viewed authorship and the dissemination of literary works. Notably, the author discusses the distinct nature of literary production in various ancient societies, setting the stage for a deeper exploration of the topic throughout the book. (This is an automatically generated summary.)s
Release date is 2024-02-10
deaurider, Eleni Christofaki and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Books -- History -- To 400; Literature, Ancient -- Criticism, Textual; Literature, Ancient -- Appreciation; Literature, Ancient -- Manuscripts; Authors and readers -- History; Authorship -- History